Implementasi Surah Al-Hasyr dengan Algoritma Dijkstra dalam Menentukan Rute Terpendek pada Perencanaan Distribusi Beras di Jawa Tengah - Azka Najmira Fauzi; Aria Hana Fazila; Asma Adibah Mawla; Arifin Aji Nugroho; Yesi Yuliani (Jurnal Integrasi Sains dan Quran, 2025)
Central Java is the second largest rice-producing province in Indonesia. However, it is unfortunate that the rice yield cannot be maximally utilized by the province itself. This is because more rice is distributed to Jakarta than to Central Java, causing the province to experience a prolonged deficit since 2022. This problem affected the price of rice in Central Java, which experienced inflation because Central Java residents had to buy rice from Jakarta. This unequal distribution is also not in accordance with QS. Al-Hasyr (59): 7, which instructs to distribute wealth equally, so that it does not circulate among the rich only. The purpose of this research is to apply Dijkstra's Algorithm in determining the shortest route in rice distribution planning in Central Java. The data in the research used is secondary data obtained through Google Maps and Google Earth. Then, the data is compiled into a weighted graph which is processed by Dijkstra's Algorithm with the help of a program in Wolfram Mathematica software. The results obtained are the shortest route from the starting point to the cities in Central Java. The results obtained can be used as a reference by rice producers in Central Java, so that the distribution of rice in the province is more efficient both in terms of costs and routes, and more equitable.